If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(x + 4) = 12 Reorder the terms: 2x + 3(4 + x) = 12 2x + (4 * 3 + x * 3) = 12 2x + (12 + 3x) = 12 Reorder the terms: 12 + 2x + 3x = 12 Combine like terms: 2x + 3x = 5x 12 + 5x = 12 Add '-12' to each side of the equation. 12 + -12 + 5x = 12 + -12 Combine like terms: 12 + -12 = 0 0 + 5x = 12 + -12 5x = 12 + -12 Combine like terms: 12 + -12 = 0 5x = 0 Solving 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '5'. x = 0 Simplifying x = 0
| -6k+8=-5k | | r^3-3r^2+2=0 | | G(x)=2x^2-6x-18 | | 4x^3+6x^2-18x+18=0 | | (-12x+6)+(x-15)= | | .94(x-2)=.02(6x-3)-.02 | | 0=-157+0.05v^2 | | -4(4p+2)-12=3(2p+8) | | x+50+3x=90 | | 3(c-1)+8=14 | | 5x-55=35 | | (9x+12)-(2x+8)= | | -11r=4r+55 | | -7x(t+4)=0 | | 8t+6t-t= | | 9-1/4n=15 | | y+2=4y+1 | | 113.0=3.14r^2 | | n=-8n-7n | | 1=22 | | 7-4[2-(3y-5)]= | | 2q+369=853 | | x+3.07+x=74.87 | | 3(1t-7)=6t | | 7y-26=-61 | | 5x+2x=65 | | 6=x^0-x | | -4(-3z)=72 | | 4(u-2)=7u+7 | | 5-2(-7+6)=14 | | x+y+z=62x-3y+5z=1 | | 3(2x-3)+4=6x+4(3x-5) |